PENGARUH FEE AUDIT, AUDIT TENURE DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEKS TAHUN 2016–2020 - Agustina Mutia; Khairiyani; Ratih Kumala Dewi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
Shariah audit quality is all the possibilities where when the auditor audits the client's financial statements they can find violations or fraud that occur in the reporting system that is not in accordance with accounting principles and Islamic principles. The purpose of this study was to determine and examine audit fees, audit tenure and company size on sharia audit quality in companies listed on the Jakarta Islamic Index. The population in this study are companies listed on the Jakarta Islamic Index from 2016-2020. Sampling using purposive sampling method in accordance with the criteria for the determination of the sample. The number of samples used in this study were 40 samples with 8 companies and 5 years of research period. The analysis used is logistic regression analysis. The results of the study show that the coefficient of determination has a value of 0.240 or 24%, which means that audit quality can be explained by the three variables by 24%, while the rest is influenced by other variables outside the study. The results also show that the audit fee variable and firm size have no effect on audit quality, while the audit tenure variable has a negative coefficient on sharia audit quality. Keywords: Audit Fees, Audit Tenure, Company Size, Sharia Audit Quality